2007
DOI: 10.1007/s11595-006-3394-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aluminum ions implantation on corrosion behavior of zircaloy-2 alloy in 1 M H2SO4

Abstract: The specimens were implanted with aluminum ions with fluence ranging from 1×10 16 to 1× 10 17 ions/cm 2 to study the effect of aluminum ion implantation on the aqueous corrosion behavior of zircaloy-2 by metal vapor vacuum arc source (MEVVA) at an extraction voltage of 40 kV. The valence states and depth distributions of elements in the surface layer of the samples were analyzed by X-ray photoelectron spectroscopy (XPS) and Auger electron spectroscopy (AES), respectively. Transmission electron microscopy (TEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The components Rct and QdL account for the electrochemical processes at the passive layer/solution interface, and they determine the impedance behavior in the high frequency range of the spectrum. The capacitance values associated with QdL are typical of those related to the double layer capacitance of passive oxide layers in all cases [45][46][47][48]: further confirmation for the assignment of the RpL and QpL parameters to describe the properties of the passive layer. In general, a very good agreement was reached between the fitted data and the experimental data for the ZrNbTiAl samples (χ 2 values between 10 -4 and 10 -5 ).…”
Section: Electrochemical Characterizationsupporting
confidence: 61%
See 1 more Smart Citation
“…The components Rct and QdL account for the electrochemical processes at the passive layer/solution interface, and they determine the impedance behavior in the high frequency range of the spectrum. The capacitance values associated with QdL are typical of those related to the double layer capacitance of passive oxide layers in all cases [45][46][47][48]: further confirmation for the assignment of the RpL and QpL parameters to describe the properties of the passive layer. In general, a very good agreement was reached between the fitted data and the experimental data for the ZrNbTiAl samples (χ 2 values between 10 -4 and 10 -5 ).…”
Section: Electrochemical Characterizationsupporting
confidence: 61%
“…Simultaneously, the behavior of new Zr-Nb, Zr-Ta, Zr-Nb-Ti, Zr-Nb-Ta, Zr-Nb-Mo, Zr-Nb-W alloy combinations were investigated by other groups with the same aim of improving the corrosion resistance of Zr-based materials [10,14,47]. Thus, it was demonstrated that the corrosion resistance of Zircalloy-2 alloy in 1 M H2SO4 was improved after the implantation of Al ions under certain process conditions [48]. Finally, since metallic materials for structural biomedical application must meet additional requirements in terms of their mechanical and magnetic properties, in addition to corrosion resistance, new alloys from the Zr-Nb, Zr-Sn, Zr-Ta, Zr-Si, Zr-Mo, Zr-Mo-Ti, Zr-Nb-Ti, Zr-Nb-Ti-Mo-Sn systems have also been proposed [7,[10][11][12]16,17,[49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…To solve such fuzzy uncertainty problems, the previous unremitting efforts promote continuous improvement and development of the fuzzy mathematics and fuzzy reasoning. Some basic concepts and principles such as fuzzy sets and comments sets involved in this study can be refered to the reference [7].…”
Section: Basic Concepts About Fuzzy Reasoning and Fuzzy Logicmentioning
confidence: 99%
“…According to the fuzzy fault diagnosis model in reference [7],if we use them to the motherboard repair, we can get a matrix. For example, given that there are (fault x i ) 2000 parts in the motherboard system, and unhealthy phenomenon (symptoms y j ) accumulatively classifies for 100 kinds.…”
Section: Discussing and Building Modelmentioning
confidence: 99%